Analisis Tanggung Jawab Kepala Desa dalam Pembangunan Berkelanjutan melalui Ekonomi Sirkular dalam Pengelolaan Sampah : (Studi di Desa Pematang Johar Kec Labuhan Deli Kab Deli Serdang) (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the implementation of the responsibilities of the village head and village government in carrying out sustainable development programs through waste bank management in accordance with the provisions of the applicable laws and regulations, with a case study in Pematang Johar Village, Labuhan Deli District, Deli Serdang Regency. The research employs a normative-empirical method with a qualitative approach to provide an in-depth analysis of both legal aspects and their practical implementation. The data used consist of primary and secondary sources, collected through observation, interviews, and documentation. Data were analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and verification or conclusion drawing. The findings indicate that the discontinuation of sustainable development programs in waste bank management has created complex and detrimental impacts on community life. The study further reveals that the responsibilities assumed by the village government have not been optimally fulfilled to ensure the success of the program. Beyond the issue of government accountability, limited allocation of village funds has hindered program implementation. Consequently, the program has gradually imposed greater burdens on the community, as operational costs remain largely the responsibility of local residents.